Design and Economic Analysis of a Photovoltaic System: A Case Study - Oko, COC; Diemuodeke, E.O; Omunakwe, E.O; Nnamdi, E (Center of Biomass & Renewable Energy, Diponegoro University, 2012)
This paper presents the design analysis of a photovoltaic (PV) system to power the CAD/CAM Laboratory at the Department of Mechanical Engineering, University of Port Harcourt. Life cycle cost and break-even point analyses are also carried out to assess the economic viability of the system. The unit cost of electricity for the designed PV system is high compared to the current unit cost of the municipally supplied electricity, but will be competitive with lowering cost of PV system components and favourable government policies on renewable energy. The approach and data provided are useful for designing solar systems in the area. The automated MS Excel spreadsheet developed could be used for the design and economic analyses of PV system in any other geographical region once the input data are sorted. Since about 90% of businesses in Nigeria currently own diesel generators, it is expected that future work should be devoted to the optimum combination of PV-Battery-Diesel system in electricity generation for optimum economic benefits to the country.Â Keywords: photovoltaic system design, renewable energy technology, solar energy economics